DOI: 10.14232/phd.775
|View full text |Cite
|
Sign up to set email alerts
|

Communities of practice and English as a lingua franca: A study of Erasmus students in Szeged

Abstract: The aim of my dissertation is to describe the complexities of English as a lingua franca (ELF) as it is used by a group of Erasmus exchange students engaged in social practice. My research was begun while I was working with the LINEE project, which made me realize that for a better understanding of the Erasmus exchange students' linguistic situation, the analytic focus had to be on language use in its social context. To that end, I adopted the community of practice model, which relies quite specifically on eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…Overall, it appears that the simple fact of living some time abroad is not enough to change deeply rooted attitudes and views. This is in line with what had already been stated by Papatsiba (2006), Byram (2008 and Kalocsai (2014) with regard to the need to prepare students prior to their mobility experiences, in order to fully benefit from them.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, it appears that the simple fact of living some time abroad is not enough to change deeply rooted attitudes and views. This is in line with what had already been stated by Papatsiba (2006), Byram (2008 and Kalocsai (2014) with regard to the need to prepare students prior to their mobility experiences, in order to fully benefit from them.…”
Section: Resultssupporting
confidence: 91%
“…This has already been studied by Kalocsai (2014) but further research is needed. Additionally, the current study has shown that the experience does not encourage the perspective of future professional mobility, but no answers are provided as to the actual reasons for this to happen.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, while recognising the influence of pre established relationships, it is crucial that the connections between language and culture are explored as situated in the instances of communication investigated. One approach within ELF studies has been to make use of the notion of commu nities of practice to account for the temporary and transient communities often associated with communication through ELF (Seidlhofer 2007, Seidlhofer 2011Cogo and Dewey 2012;Kalocsai 2014). However, with the exception of Ehrenreich (2009) and Kalocsai (2014), there has been little empirical exploration of how the concept can add to our understanding of ELF data and in particular there has been almost no discussion of how culture, community, and communication might interrelate.…”
Section: Culture In Intercultural Communication Through Elfmentioning
confidence: 99%
“…Two studies inquired into natural discourses. Kalocsai (2011) examined the complexities of English as a lingua franca (ELF) used by 142 Erasmus exchange students engaged in social practices. Her ethnographic study analysed audio-taped interviews and observational data, field notes, Facebook posts and email messages.…”
Section: Focal Pointsmentioning
confidence: 99%